Development and validation of the General Risk Propensity Scale (GRiPS) - Zhang, Don C.; Highhouse, Scott; Nye, Christopher D. (Journal of behavioral decision making, 2019)
Despite the widespread interest in understanding and identifying risk takers by psychologists, clinicians, and economists, the risk literature currently lacks consensus regarding the nature of risk taking and its measurement. Existing measures of risk taking are predominantly domain‐specific despite emerging support for risk taking as a domain‐general disposition. In the present paper, we examine the nature of risk taking as a domain‐general personality disposition and develop a concise measure: the General Risk Propensity Scale (GRiPS). Data from 1,523 participants across five studies provided evidence for its construct validity. The GRiPS converged with other self‐report measures of risk taking and provided incremental prediction of work, academic, and life outcomes over and above the five‐factor model of personality and the Domain‐Specific Risk Taking Scale.